Diagnóstico de enfermagem em crianças hospitalizadas utilizando aTaxonomia II da Nanda-I - Leon, Pollyana Amorim Ponce de (2011)
Introduction: The Nursing Diagnosis is part of an organized system, to carry out a model of assistance to preserve and refresh the human quality of life, especially children, because of their higher vulnerability, and has also the function to set a standard when it comes to nurse care with children, this way, providing more attention to a given population. Objective: To identify, by applying the Taxonomy II from NANDA International (NANDA-I), nursing diagnoses for children from 0 to 5 years old, hospitalized in a Pediatric Clinic of a school hospital, and analyze which risk factors or defining characteristics that show relevance to the most frequent nursing diagnoses from the sample of children from 0 to 5 years old, hospitalized in a Pediatric Clinic of a school hospital. Method: It is a case study, with a quantitative approach to the data analysis. 37 hospitalized children were part of the sample which filled out the following inclusion criteria: to be in the age group from 0 to 5 years old and cannot be hospitalized for the second time. The instrument used was developed by Silva (2004), entitled History of Nursing for Children from 0 to 5 years old , based on the Theory of Basic Human Needs by Horta. The data collected went through a judging process of the answers given by each child, which resulted in individual charts, with the affected needs, the empiric indicators identified and the nursing diagnoses, that were done by using the process of clinic reasoning by Gordon (1994) and the Taxonomy II from NANDA-I. Results: The data of the study show that a large part of the participants in the study were infants, from the City of Joao Pessoa. With respect to education level of companions, the majority had not completed basic. On the basis of the diagnoses obtained the damaged skin integrity presented the most frequent, followed by Risk of infection, Risk of electrolyte imbalance, and Acute pain. Final considerations: Using nursing diagnoses based on a theoretic model, following a terminology strengthens the nursing assistance for the continuity of the steps of the Nursing Process and identifying the defining characteristics and the risk factors demands from the nurse a practical and scientific knowledge, which will result in a qualified and humane care towards the child. It is expected that this research will arouse new studies in this field, which is in need, each day, of interested, capable and with critical thinking professionals, to execute the complex activities.